Characterisation of odour-active compounds in lupin flour - Bader, Stephanie; Czerny, Michael; Eisner, Peter; Büttner, Andrea (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Lupin ingredients are promising alternatives to soybean products owing to their similarly high protein content. Lupin flour exhibits a green and bean-like off-flavour in higher amounts. The aim of this study was to characterise and identify the main odour-active compounds in lupin flour. RESULTS: The orthonasal aroma of lupin flour was evaluated by means of aroma profile analysis and was found to be characterised by grassy-green, metallic, fatty, fruity, hay-like, cheese-like, and meat-like odour qualities. Volatile compounds of lupin flour of Lupinus angustifolius cv. Boregine were extracted with dichloromethane and isolated by solvent-assisted flavour evaporation. Aroma extract dilution analysis (AEDA) was carried out with the obtained extract. In total, 50 odorants were detected by high-resolution gas chromatography-olfactometry. AEDA revealed 26 odour-active compounds with flavour dilution factors higher or equal to 32. The substances were unequivocally identified by their odour characteristics, their retention indices and their mass spectra using one-dimensional or two-dimensional gas chromatography-mass spectrometry, respectively. CONCLUSION: A series of unsaturated and saturated aldehydes, ketones, carboxylic acids, alkyl-methoxypyrazines and terpenes were identified for the first time as odour-active contributors to the aroma of lupin flour. © 2009 Society of Chemical Industry.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.charac_8
Keywords: Aroma extract dilution analysis (AEDA); Gas chromatography-mass spectrometry (HRGC-MS); High-resolution gas chromatography-olfactometry (HRGC-O); Lupinus angustifolius cv. Boregine; Two-dimensional HRGC-MS